Dyadic death-an unusual case of post-mortem mutilation - Navneet Ateriya; Ashish Saraf; Tanuj Kanchan; Raghvendra Singh Shekhawat (Egyptian Journal of Forensic Sciences, 2018)
Abstract Background Dyadic suicides comprise of suicides occurring simultaneously or one after another in two or more people, either with an agreement or without one. Firearms, poisoning, hanging, and drowning are the preferred methods of suicide employed in such cases. Investigation of dyadic deaths remains a challenge for the investigators especially in concluding on the cause and manner of death. Case presentation We report a case of dyadic suicide where hanging was used by a couple to end their lives. Post-mortem mutilation of the tongue in female and ante-mortem injuries to the fingertips in male helped in the reconstruction of events in this case. Conclusion Death scene reconstruction and exploring the sequence of events prior to the death are paramount in the investigation of dyadic deaths not only to conclude on the exact cause and manner of death but also to ascertain if the deaths were simultaneous or one after another.